The grape pomace Italia as a source of bioactive compounds and its lever- aging in the obtaining of ethanol and compost. - COTACALLAPA-SUCAPUCA, M. (Universidad Nacional del Litoral, 2020)
The pomace of the wine industry currently represents a waste management problem due to its high pollution load; however, it is a source of functional elements, ethanol and compost. Pomace was fermented twice, after which total phenolics and fl avonoids were quantifi ed in triplicate. The liquid obtained together, was distilled in differential systems and optimized with rectifi cation. Subsequently, the pomace was composed with three replicates, to which effi cient natives microorganisms were applied. Total phenolics are signifi cantly different between fi rst and second fermentation, while fl avonoids have no signifi cant differentiation. Optimization parameters for alcoholic degrees were; refl ux system, heating power and water fl ow rate for condensate, obtaining 81.47 alcoholic degrees. The composting time lasted 21 days, shorter than other methods. These results refl ected the importance of pomace exploitation as a food, energy and agricultural source.